ANALISIS PEMBELAJARAN PROJECT BASED LEARNING MELALUI PRAKTIKUM PENGUKURAN KAPASITAS PARU-PARU PADA MATERI SISTEM PERNAPASAN DI PESANTREN DARUT THOLIBIN SERDANG BEDAGAI - Amelia Patra Harahap; Asih Maulida Hasni; Grace Violencia Sinaga; Sri Wahyuni Siregar; Widya Arwita; Rizal Mukra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of student activeness and learning outcomes in the respiratory system topic, caused by teacher-centered learning and limited instructional media. The purpose of this study is to describe the implementation of the Project Based Learning (PjBL) model through a lung capacity measurement practicum and its impact on student activeness and learning outcomes. This research employed a qualitative descriptive approach conducted at Pesantren Darut Thalibin Serdang Bedagai, involving eleventh-grade students and a biology teacher as research subjects. Data were collected through interviews, observations, documentation, as well as pretest and posttest. The results indicate that before the implementation of PjBL, students tended to be passive and had low understanding of the material. After the implementation of PjBL through practicum activities, students became more active, enthusiastic, and engaged in the learning process. In addition, there was an improvement in student learning outcomes as reflected in the comparison between pretest and posttest results. Therefore, the implementation of the PjBL model through lung capacity measurement practicum can enhance student activeness and learning outcomes in the respiratory system topic.